2009
DOI: 10.1007/s12564-009-9001-8
|View full text |Cite
|
Sign up to set email alerts
|

Goals, components, and factors considered in university development

Abstract: It is generally known that the general goals of universities are to produce high-quality graduates for the job market, to continuously advance the frontier of knowledge in all the disciplines, and ultimately to advance human civilization. There can, however, be numerous specific goals which differ from one university to the other. Whatever it is, in order to achieve the desired goals, universities need to design a realistic strategic development plan, which must include, among others, the important logistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…encompass main components such as finance, services, human resources, research, and infrastructure. Based on these plans, universities can deliberate on what they want to achieve, the way by which the tasks must be completed, the time of achieving the goals, deciding on who are accountable for carrying out the plans, as well as the required facilities and funds needed for materializing the aspired goals (Hussin and Ismail 2009). In this situation, effective leaders play a significant role in providing the necessary guidelines and taking crucial actions for effective implementation of the programs.…”
Section: Introductionmentioning
confidence: 99%
“…encompass main components such as finance, services, human resources, research, and infrastructure. Based on these plans, universities can deliberate on what they want to achieve, the way by which the tasks must be completed, the time of achieving the goals, deciding on who are accountable for carrying out the plans, as well as the required facilities and funds needed for materializing the aspired goals (Hussin and Ismail 2009). In this situation, effective leaders play a significant role in providing the necessary guidelines and taking crucial actions for effective implementation of the programs.…”
Section: Introductionmentioning
confidence: 99%
“…The dichotomy between local historical, socio-cultural, and political development components of universities. In this case, policy reform generally focuses on academic programs, research and consultancy, post-graduate scholarships, research, instruction and learning, management, human resources management, finance, infrastructure and facilities, student services and development (Hussin & Ismail, 2009). This paper focuses on the cultural dimensions of both Asian and Cambodian history, traditional values, and socio-cultural aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Student-focused goals enable learners to evaluate an unfamiliar event in a profession and acquire needed competencies for analysis, design, prototype development, testing, improvement, mass production, marketing, and maintenance and develop student-centered goals. Sufean Hussin, Aziah Ismail, and Jung Cheol Shin [19] stated that universities employ strategic development planning to identify the specific goals, components, and factors of development. Further, they concluded that a wellformulated strategic development plan will ensure synchronized development programs and activities throughout a university system.…”
Section: Literature Surveymentioning
confidence: 99%